Cross-cultural teaching and learning methodology analysis for Asian students in Australian universities - Lu, J.; Chin, Kum; Yao, J.; Xu, J.; Xiao, J. (Universiti Teknologi MARA Terengganu, 2009)
The number of Asian background international students in Australian universities has been increasing dramatically in the last ten years. The cultural factors may affect the learning outcomes of international students and the teaching approaches adopted by Australian lecturing staff. Therefore, the cross-cultural teaching and learning environment becomes an important issue in some education units of Australian universities. This study has completed a questionnaire survey of 1026 students from five universities in Australia. The questionnaire includes 55 main questions within six sections. Within the 1026 students, there are 639 Asian background international students and 387 others. These students mainly study in Information Technology field (28.5%) and Business field (52.5%). We have conducted statistical analysis including frequency and Chi-Square to test 59 hypotheses we defined. We have also analyzed the open questions in the questionnaire. This paper mainly presents the research methodology, main data analysis results and interesting findings of this project.